2016
DOI: 10.4314/wsa.v42i1.04
|View full text |Cite
|
Sign up to set email alerts
|

Understanding farmers’ preferences for wastewater reuse frameworks in agricultural irrigation: lessons from a choice experiment in the Western Cape, South Africa

Abstract: Wastewater has emerged as an alternative source of water. Since the agricultural sector remains the largest water user world-wide, it is the main potential user of treated wastewater. However, while there are trade-offs in using wastewater, it may be the only option in water-scarce regions. South Africa has included water reuse as a policy option; hence the aim of this study is to understand farmers' preferences regarding water reuse frameworks for irrigation. A choice modelling approach was applied to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The heterogeneity in preferences show that more than 99% of the farmers have a great interest in using organic matter and are WTP on average, about 120,000 F CFA (US$190.3) per ha for RRR solutions that feature this attribute. This is in line with many previous studies, which have shown that the recovery and reuse of wastes can contribute substantially to reducing poverty, improving food security and managing natural resources more sustainability to protect ecosystems and build climate-resilient communities [54,55].…”
Section: Discussion and Policy Implicationssupporting
confidence: 91%
“…The heterogeneity in preferences show that more than 99% of the farmers have a great interest in using organic matter and are WTP on average, about 120,000 F CFA (US$190.3) per ha for RRR solutions that feature this attribute. This is in line with many previous studies, which have shown that the recovery and reuse of wastes can contribute substantially to reducing poverty, improving food security and managing natural resources more sustainability to protect ecosystems and build climate-resilient communities [54,55].…”
Section: Discussion and Policy Implicationssupporting
confidence: 91%
“…Approaches for measuring WTP or WTA (economic valuation) can be placed in two broad categories: the revealed preference (RP) and the SP methods. Most of the studies reviewed could have applied SP methods because these methods are able to estimate both the use and the nonuse values of a product or a service, compared to the RP approaches that measure only the use values (Bozorg-Haddad et al, 2016; Saldías et al, 2016). In fact, most studies measured WTP for water and environmental improvement innovations.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed, water reclamation is regarded an affordable alternative for many water-scarce regions (Saldías et al, 2016) and a reliable provision of a consistent nutrient source (Akponikp� e et al, 2011;Miller--Robbie et al, 2017;Scott et al, 2004). Given the aforementioned accessibility to wastewater streams, irrigation tends to be an important endpoint for untreated or (partially) treated wastewater in many developing countries (Al-Hamaiedeh and Bino, 2010;Jaramillo and Restrepo, 2017;Keraita et al, 2008;Raschid-Sally et al, 2005;Scott et al, 2004).…”
Section: Global Trends For Water Reclamation In Agriculturementioning
confidence: 99%